Decrease of server loads on the computer Network using the principle of cache (Damascus University Journal for engineering sciences, 2021)
The diversity of networks infrastructures, swell its size, increasing number of its investors and increasing the size of data transferred by it, in addition to the increasing popularity of the Web has led to noticeable increasing in the amount of traffic on the internet, which in turn led to creation of many problems such as bottlenecks, slow data transfer and  servers overload leading to Delay user access to their data on the network , either because of  the servers receiving requests more than it can handed it, or because of congestions network path between the user and the server which in turn leads to lower network performance as a whole.Here there was a need to use the concept of Web Caching to save a copy of web content close to end user and thus improve the efficiency of browsing the Web as well as decrease of server loads and many other features provided by this technique.This research aims to study ways to cache web pages and what is its impact in improving users’ access to their data over the network and thus improve the network performance as a whole. We focus on this research on proxy cache method to cache web content where the application of this research has been on two infrastructures and the results was taken from proxy servers available on the network.
Keywords: Networks, servers; caching web content; cache; ICP; network path